The Effect Of Training And Competency Development On Personnel Performance With Job Satisfaction As An Intervening Variable In UPT. Firefighter Dairi Regency - Amudi Parulian Situmeang; Kiki Farida Farine (International Journal of Management, Economic and Accounting, 2025)
Personnel Performance is influenced by various factors, including Training and Competency Development provided by the organization. Effective training and relevant competency development programs can improve Job Satisfaction, ultimately contributing to improved performance. This study aims to identify the influence of Training and Competency Development on Personnel Performance by considering the role of Job Satisfaction as an intervening variable in UPT. Dairi Regency Fire Department. Data was obtained through a survey with a quantitative approach and analyzed using the Partial Least Squares (PLS) method. The results of the analysis showed that Training had a positive and significant influence on Job Satisfaction with a T-Statistic value of 4.215 and a P-Value of 0.000. However, the direct influence of Training on Personnel Performance showed significant negative results with a T-Statistic value of 4.572 and a P-Value of 0.000. Competency Development is proven to have a positive and significant influence on both Job Satisfaction (T-Statistic 3.525, P-Value 0.001) and Personnel Performance (T-Statistic 4.652, P-Value 0.000). In addition, Job Satisfaction has a positive and significant influence on Personnel Performance, with a T-Statistic value of 4.324 and a P-Value of 0.000. Indirect influence analysis shows that Training and Competency Development have a significant effect on Personnel Performance through Job Satisfaction as a mediating variable. These findings indicate that the improvement of Training and Competency Development will be more effective in driving Personnel Performance when facilitated by high Job Satisfaction. Suggestions are given to institutions to improve training methods and strengthen competency development programs, as well as consider increasing job satisfaction as an effort to optimize performance. The researcher is further advised to explore other intervening variables that may play a role in improving personnel performance.